2005
DOI: 10.2174/1568007054546162
|View full text |Cite
|
Sign up to set email alerts
|

Old and New Drug Targets in Diabetic Retinopathy: From Biochemical Changes to Inflammation and Neurodegeneration

Abstract: Diabetic Retinopathy (DR) is a major complication of diabetes and is a leading cause of blindness in western countries. DR has been considered a microvascular disease, and the blood-retinal barrier breakdown is a hallmark of this disease. The available treatments are scarce and not very effective. Despite the attempts to control blood glucose levels and blood pressure, many diabetic patients are affected by DR, which progresses to more severe forms of disease, where laser photocoagulation therapy is needed. DR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 192 publications
(231 reference statements)
1
15
0
Order By: Relevance
“…4B and C), consistent with requirement of STAT3 for transcription of VEGF and HIF-1␣ mRNA (35,36,44). While VEGF may provide prosurvival functions in retina, accumulation of VEGF in the eye is implicated in the development of retinopathies, and anti-VEGF antibody is effective in treatment of diabetic retinal neovascularization (45). These diametrically polar effects of VEGF in the retina suggest that STAT3-induced VEGF expression is exquisitely regulated in the retina, as activated STAT3 is preferentially localized to neovascular retinal vessels in a mouse model of ischemia-induced retinal neovascularization (46).…”
Section: Discussionsupporting
confidence: 63%
“…4B and C), consistent with requirement of STAT3 for transcription of VEGF and HIF-1␣ mRNA (35,36,44). While VEGF may provide prosurvival functions in retina, accumulation of VEGF in the eye is implicated in the development of retinopathies, and anti-VEGF antibody is effective in treatment of diabetic retinal neovascularization (45). These diametrically polar effects of VEGF in the retina suggest that STAT3-induced VEGF expression is exquisitely regulated in the retina, as activated STAT3 is preferentially localized to neovascular retinal vessels in a mouse model of ischemia-induced retinal neovascularization (46).…”
Section: Discussionsupporting
confidence: 63%
“…Some studies strongly suggest that retinal macroglia and microglia may be associated with retinal dysfunctions such as vitreoretinopathy, diabetic retinopathy, retinitis pigmentosa and age-related macular degeneration (Gupta et al, 2003;McGillem and Dacheux, 1998;RunggerBrandle et al, 2000;Soler et al, 2002). Therefore, the presence of NPY in retinal microglia may suggest a putative role of this peptide on inflammatory states observed in those retinal dysfunctions and should be further investigated (Leal et al, 2005;Meleth et al, 2005;Zhou et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…However, if early neural damage occurs, it can be studied by searching for evidence of neuroretinal changes in the absence of retinal microvasculopathy. This is possible in the pre-DR stage (14)(15)(16)(17). Some functional studies have suggested visual impairment in diabetic patients without apparent DR, but these studies did not exclude changes in integrity of the barrier function using a quantitative method (2,(18)(19)(20)(21)(22)(23)(24)(25).…”
mentioning
confidence: 99%